Emerging Threats in Wireless Network Security: A Contemporary Analysis - Divya Dhanraj Fande; Sushil Bakhtar (International Journal of Satellite Remote Sensing, 2024)
A crucial component of the architecture of contemporary information technology is wireless network security, as wireless communications .Given the continued importance of wireless communication in today's information technology architecture, wireless network security Since wireless communication is becoming more and more essential to our everyday lives, wireless network security is an essential component of today's information technology infrastructure. An overview of the main ideas, problems, and solutions for protecting wireless networks is given in this abstract. Wireless networks, including cellular networks, Wi-Fi, and Bluetooth, are now commonplace, linking a wide range of devices and facilitating smooth communication. But because of their intrinsic weaknesses, they are open to several kinds of security risks, such as denial-of-service attacks, illegal access, eavesdropping, and data leaks. Wireless network security uses a variety of methods and protocols to overcome these issues. Wi-Fi authentication protocols like WPA2/WPA3 aid in confirming the legitimacy of connected devices. Protocols for encryption, such as WPA, WPA2, and WPA3/WPA3, safeguard data while it's in transit and guarantee confidentiality. Potential risks are identified and lessened with the aid of intrusion prevention systems (IPS) and intrusion detection systems (IDS). Network segmentation, which separates critical data from public networks, and frequent security audits to find weaknesses are other important techniques in wireless network security. Maintaining a secure wireless environment also requires the use of virtual private networks (VPNs), strong password policies, and frequent firmware updates. New security difficulties are brought forth by emerging technologies like 5G and the Internet of Things (IoT), which necessitate constant innovation in wireless network security. Because more and more businesses and individuals depend on wireless connectivity, it is critical to secure these networks to preserve sensitive data and guarantee the reliability and accessibility of wireless services.
Keywords: Internet of things (IoT); Virtual Private Networks (VPNs); Wireless; communication; network security; router